RpoN2- and FliA-regulated fliTX is indispensible for flagellar motility and virulence in Xanthomonas oryzae pv. oryzae - Chao Yu; Huamin Chen; Fang Tian; Fenghuan Yang; Chenyang He (BMC Microbiology, 2017)
Abstract Background Bacterial blight of rice caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most important crop diseases in the world. More insights into the mechanistic regulation of bacterial pathogenesis will help us identify novel molecular targets for developing effective disease control strategies. A large flagellar gene cluster is regulated under a three-tiered hierarchy by σ54 factor RpoN2 and its activator FleQ, and σ28 factor FliA. A hypothetical protein gene fliTX is located upstream of rpoN2, however, how it is regulated and how it is related to bacterial behaviors remain to be elucidated. Results Sequence alignment analysis indicated that FliTX in Xoo is less well conserved compared with FliT proteins in Escherichia coli, Salmonella typhimurium, and Pseudomonas fluorescens. Co-transcription of fliTX with a cytosolic chaperone gene fliS and an atypical PilZ-domain gene flgZ in an operon was up-regulated by RpoN2/FleQ and FliA. Significantly shorter filament length and impaired swimming motility were observed in ∆fliTX compared with those in the wildtype strain. ∆fliTX also demonstrated reduced disease lesion length and in planta growth in rice, attenuated ability of induction of hypersensitive response (HR) in nonhost tobacco, and down-regulation of type III secretion system (T3SS)-related genes. In trans expression of fliTX gene in ∆fliTX restored these phenotypes to near wild-type levels. Conclusions This study demonstrates that RpoN2- and FliA-regulated fliTX is indispensible for flagellar motility and virulence and provides more insights into mechanistic regulation of T3SS expression in Xoo.